Embriotoxic effects of Picrosia longifolia Don (ASTERACEAE) - Benavides, Victor (2001)
The toxic effects of aquous extract of Picrosia longifolia Don “achicoria” on preimplantational mouse embryo development were evaluated. Aquous extract of P. longifolia to 20%, 10% and 0% (control group) was supplied to pregnant mice to 86 hours post-copula (hpc). When embryonic stage was evaluated, we found that aquous extract of P. longifolia to 10% and 20% causes delay in embryo development. Also the embryonic viability declined in treated groups with achicoria.